The Contours of Constitutional Approval - Nicholas O. Stephanopoulos; Mila Versteeg (Washington University Law Review, 2016)
Scholars and judges agree on the importance of constitutional approval—that is, people’s subjective support for their constitution. The Supreme Court has asserted that it owes its very legitimacy to popular backing for its decisions. Academic luminaries have concurred, while also connecting constitutional approval to constitutional compliance and durability, as well as the easing of the countermajoritarian difficulty. Until now, though, no information has been available on either the levels or the causes of constitutional support. In this Article, we rectify this shortcoming by presenting the results of a nationally representative survey that we conducted in late 2014. The survey asked respondents about their approval of the federal Constitution and of their state constitution, and about several potential bases for support. We also supplemented the survey by coding dozens of features of state constitutions. This coding allows us to test hypotheses about the relationship between constitutional content and constitutional backing. What we find is illuminating. First, people highly approve of their constitutions—the federal charter more so than its state counterparts. Second, approval is unrelated to what constitutions say; it does not budge as their provisions become more or less congruent with respondents’ preferences. Third, approval is only weakly linked to respondents’ demographic attributes. And fourth, the most potent drivers of approval are constitutional familiarity and pride in one’s state or country. To know it—and to be proud of it—is to love it. These results unsettle several literatures. They mean that people form opinions about constitutions differently than about other institutions. They also mean that comparativists may be going down a blind alley as they focus ever more intently on constitutional design. But perhaps our study’s clearest implication is for leaders who value popular support for their constitution. Our advice to them is to forget about constitutional change, and instead to try to build the public’s knowledge and appreciation of the charter. Constitutional approval, like statecraft, is ultimately a project of soulcraft.
Keywords: constitution; popular approval; Supreme Court; public opinion; governmental comparison